Flight dynamics - Stengel, Robert F. (Princeton University Press, 2022)
"Flight Dynamics, first published in 2004, took a new approach to the science and mathematics of aircraft flight, unifying principles of aeronautics with contemporary systems analysis. While presenting traditional material that is critical to understanding aircraft motions, it does so in the context of modern computational tools and multivariable methods. Robert Stengel devotes particular attention to models and techniques that are appropriate for analysis, simulation, evaluation of flying qualities, and control system design. He establishes bridges to classical analysis and results, and explores new territory that was treated only inferentially in earlier books. The second edition will provide updates that cover new developments in aviation. Substantive changes include the addition of examples that relate to contemporary aircraft types, such as uninhabited air vehicles (UAVs), electrically powered airplanes, blended wing-body configurations, supersonic and hypersonic cruisers, and sub-orbital aerospace planes"-- Provided by publisher.
Keywords: Aerodynamics.; Flight.; Airplanes -- Performance.; elektronické knihy; electronic books